Preprocedural Leucocyte Count Predicts Risk in Patients with Coronary Chronic Total Occlusion - Gebhard, Catherine; Toma, Aurel; Min, Zhao; Stähli, Barbara E.; Mashayekhi, Kambis; Gick, Michael; Ferenc, Miroslaw; Büttner, Heinz Joachim; Neumann, Franz-Josef (Thrombosis and Haemostasis, 2017)
Background As technologies of percutaneous coronary intervention (PCI) for coronary chronic total occlusions (CTO) have improved, great uncertainty exists regarding patient selection and long-term benefit of CTO-PCI. Given that white blood cell (WBC) count has been associated with cardiovascular risk, we hypothesized that the latter might provide incremental prognostic value in patients undergoing CTO-PCI.Methods and Results Our study population consisted of 1,262 consecutive patients (76.3% males, mean age of 67.7 ± 10.3 years) who underwent elective PCI at our centre between January 2002 and December 2008. Four hundred seventy-five patients had at least one CTO, while 787 patients with non-occlusive coronary lesions served as controls. Baseline WBC count was higher in CTO patients as compared with controls (8,072 ± 3,459/μL vs. 7,469 ± 2,668/μL, p = 0.001) and independently predicted the occurrence of a CTO lesion (odds ratio: 1.8; 95% confidence interval [CI]: 1.3–2.4; p < 0.001). After a median follow-up of 3.1 years (interquartile range: 2.1–4.2 years), CTO patients with WBC counts ranging in the highest tertile had significantly worse outcomes than CTO patients with lower WBC counts (log-rank = 0.009 for all-cause mortality and log-rank = 0.01 for major adverse cardiac events). These associations were not seen in controls. Accordingly, elevated WBC count was identified as a significant predictor for all-cause mortality (adjusted hazard ratio: 3.1; 95% CI: 1.6–6.2; p = 0.001) in CTO patients but not in patients with non-occlusive coronary artery disease (pint = 0.088).Conclusion Assessment of the inflammatory status of CTO patients may be an important element in selecting CTO patients at low risk who may be referred to CTO-PCI.
Keywords: coronary chronic total occlusion; leucocytes; mortality